2003
DOI: 10.1073/pnas.1031521100
|View full text |Cite|
|
Sign up to set email alerts
|

Linkage disequilibrium in human populations

Abstract: Whereas the human linkage map appears on limited evidence to be constant over populations, maps of linkage disequilibrium (LD) vary among populations that differ in gene history. The greatest difference is between populations of sub-Saharan origin and populations remotely derived from Africa after a major bottleneck that reduced their heterozygosity and altered their Malecot parameters, increasing the intercept M that reflects association in founders and decreasing the exponential decline ɛ. Variation among po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
58
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 26 publications
8
58
0
Order By: Relevance
“…63,65 Conflicting evidence has, however, been reported regarding the actual degree of homogeneity of isolated populations. 64 A previous study on the Faroese population 25 indicated extensive LD among the 15 markers surveyed. Furthermore, the allelic diversity was smaller, although nonsignificant in the Faroese population compared to outbred populations.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…63,65 Conflicting evidence has, however, been reported regarding the actual degree of homogeneity of isolated populations. 64 A previous study on the Faroese population 25 indicated extensive LD among the 15 markers surveyed. Furthermore, the allelic diversity was smaller, although nonsignificant in the Faroese population compared to outbred populations.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, background LD may due to random genetic drift extend over greater genetic distances in isolated populations, thereby reducing the sample size and the number of markers needed to identify specific genes. 63,64 In addition, isolated populations may be more suitable for association mapping because of the more homogeneous environmental background. 63,65 Conflicting evidence has, however, been reported regarding the actual degree of homogeneity of isolated populations.…”
Section: Discussionmentioning
confidence: 99%
“…Linkage and LD are separate but complementary, with their different evidence as unconfounded, as is consistent with the goal of enhancing resolution of the linkage map without degrading the LD map. It remains to be determined whether one linkage map will suffice for different populations and whether a single composite LD map will be efficient for association mapping in samples with different Malecot parameters (7).…”
Section: Discussionmentioning
confidence: 99%
“…Using the HapMap data (3) to construct linkage disequilibrium (LD) maps measured in LD units (LDU) (4) and interpolating them into the sex-specific linkage map enhances the resolution of the linkage map as a by-product of our main objective, which is to construct genomewide LD maps with additive LDU distances. Such maps are applicable to association mapping (5,6), population comparisons (7)(8)(9), and identification of genomic regions that are influenced by selection (10). LD mapping has begun the task of explaining and exploiting complexities (8) that do not affect application of the Malecot model (4) to create an LD map but determine how the map should be used to increase resolution of the linkage map.…”
mentioning
confidence: 99%
“…[33][34][35][36][37][38][39] The general pattern found in the regions examined so far is a series of discrete tracts of low recombination, high LD and therefore with a reduced number of haplotypes, the so-called 'haplotype blocks' bounded by recombination hotspots. Haplotype block structure has been found to vary according to genomic region (due to genomic factors affecting its pattern) and also between different global populations (due to demographic factors), 33,36,[38][39][40][41][42][43][44] see Bertranpetit et al 45 for a review. In fact, the goal of the International HapMap Project (http://www.hapmap.org) is to develop a haplotype map of the human genome, the HapMap, which will describe the common patterns of human DNA sequence variation in four distinct human populations.…”
Section: Introductionmentioning
confidence: 99%